ENTERPRISE ECOSYSTEM AND SUSTAINABLE DEVELOPMENT: IMMANENT INTERDEPENDENCE - Maryna Nahara (Agora International Journal of Economical Sciences (AIJES), 2024)
Global hypercompetition necessitates the development of new models of business collaboration among economic entities. Enterprise ecosystem is one form of organization and support for entrepreneurship that facilitates the transition from competition to cooperation among business entities. The article explores various theoretical approaches to defining the concept of ecosystem that enabled to propose the author's interpretation. It is substantiated that the entrepreneurial ecosystem offers optimal pathways and effective tools for fostering innovation and economic growth, grounded in the principles of sustainable development. A comparative analysis of organizational models of activity is conducted. Compared to other organisational models, the ecosystem entails the transformation of hierarchical management mechanisms, giving rise to a dynamic environment facilitating the free exchange of knowledge, information, resources, technologies, and competencies. The synergistic model of the enterprise ecosystem within the framework of sustainable development is proposed. The model exhibits several characteristic features: cross-industry interaction, which maximizes synergies more effectively than corporate ties; diversification of activities with a focus on lean innovation; emphasis on environmental sustainability and the commercialization of developments; flexibility of business processes; autonomy of participants and adherence to voluntary cooperation principles. The article substantiates the key improvement strategies that enterprises should implement to achieve synergistic effects and sustainable development goals within the enterprise ecosystem.
Keywords: 330